2020
DOI: 10.3390/lubricants8040038
|View full text |Cite
|
Sign up to set email alerts
|

Shear Thinning in the Prandtl Model and Its Relation to Generalized Newtonian Fluids

Abstract: The Prandtl model is certainly the simplest and most generic microscopic model describing solid friction. It consists of a single, thermalized atom attached to a spring, which is dragged past a sinusoidal potential representing the surface energy corrugation of a counterface. While it was primarily introduced to rationalize how Coulomb’s friction law can arise from small-scale instabilities, Prandtl argued that his model also describes the shear thinning of liquids. Given its success regarding the interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…These rearrangements could be dominated by shear-assisted thermal activation [62,63]. Other mechanisms such as those originating from the elasticity of the squalane molecules as represented in the Prandtl model may also explain the origins of the shear thinning behavior at high pressures [64]. New investigations utilizing different types of high-dimensional data are required to make progress toward a more precise diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These rearrangements could be dominated by shear-assisted thermal activation [62,63]. Other mechanisms such as those originating from the elasticity of the squalane molecules as represented in the Prandtl model may also explain the origins of the shear thinning behavior at high pressures [64]. New investigations utilizing different types of high-dimensional data are required to make progress toward a more precise diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Carreau equation contains many other models as limiting cases [12], including the Eyring model [13]. While the Eyring and Carreau models predict similar shear stress (or viscosity) at low shear rates, they diverge at high shear rates [3].…”
Section: Shear Thinningmentioning
confidence: 99%
“…Additionally, in athermal case, the elastic body jumps out of contact when the spring stiffness k is less than the maximum curvature of the potential energy V ′′ max . This mechanism is analogous to that of the friction-velocity relation in the Prandtl model [14][15][16], in which a particle of mass m is dragged through a sinusoidal potential with a driving spring with velocity v. On the other hand, several experimental studies have demonstrated that the velocity can significantly affect the pull-off force [17][18][19]. In light of this fact, we expect that this model to also accurately describe the relation between pull-off force and velocity and further predict the contribution of thermal effects on this relation.…”
Section: Introductionmentioning
confidence: 80%